Dampak Konversi Lahan Pada Daerah Peri-Urban Terhadap Perubahan Mata Pencaharian Petani Tahun 2004-2024: Studi Kasus Desa Gentan, Baki, Sukoharjo - Margareta, Lauren Adellia; Andini, Isti; Rahayu, Paramita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2025)
Land conversion is a phenomenon of land conversion that causes a decrease in the proportion of a land area to other functions. In peri-urban areas that are dominated by agricultural land, its function changes to non-agricultural land due to land conversion for the construction of public facilities for the community. Especially at the location of this research study located in Gentan Village, Baki District, Sukoharjo Regency, Central Java. The existence of land conversion causes the loss of productive agricultural land so that farmers experience decreased productivity and affects farmers' livelihoods which change from agriculture to non-agriculture such as opening boarding houses, rental houses, shops, stalls and so on. This study uses a deductive quantitative approach with GIS analysis, Likert scale and Wilcoxon test to determine changes in farmers' livelihoods due to agricultural land conversion as the purpose of the study. The use of the snowball sampling technique with a quota of 32 farmers whose land was converted is based on the limitations of secondary data in the search for respondents. So that from this study it was found that land conversion causes significant changes in livelihoods that can affect socio-economic and environmental conditions.